Backgammon - Magriel, Paul, 1946- (New York : Quadrangle/New York Times Book Company, 1976)
Backgammon carefully explains the game's basic concepts, ideas and strategic principles. They have never been organized or categorized so lucidly. Although Magriel discusses theories so advanced only a few plays in the world are aware of them, this book is neither technical nor abstruse. The years of research and organization that went into the book have made Backgammon any player's gift of - and for - a lifetime.
Keywords: Backgammon